Teknik Instruksional Concept Map di Tahap Deciding - Project Based Learning terhadap Keterampilan Argumentasi Siswa - Rakhmatdi Rakhmatdi; Sri Widoretno; Joko Ariyanto; Bowo Sugiharto; Sri Dwiastuti; Chandra Adi Prabowo (Postgraduate, University of Mataram, 2023)
Argumentation is an assessment that identifies HOTs through collaborative learning activities. Learning that supports collaboration through project design is found in project-based learning at the deciding stage. Decisions in planning investigations tend to be less than optimal and the presentation of data at the deciding stage is incomplete so that it is optimized using the instructional concept map technique. The use of concept maps as an instructional technique guides students to find and relate concepts logically so as to stimulate argumentation skills because it explores critical thinking skills through activities of organizing, categorizing, analyzing, and reasoning. The research aims to analyze differences in students' argumentation skills from the use of concept map instructional techniques at the deciding stage – project-based learning. The research design was quasi-experimental. Determination of the sample using cluster random sampling of 70 students who are determined based on the paired F test. The research instrument consisted of an expert concept map and a matter of argumentation. Data on students' argumentation skills were obtained from an assessment that was arranged according to the argumentation component according to Toulmin (2003) is evidence, warrants, backing, qualifier, rebuttal, and claim a total of 11 questions. The data analysis technique used the t-test. The results of the hypothesis test show that the significance value is 0.001 (<0.05), so there are differences in students' argumentation skills from the use of the instructional concept map technique in the deciding – project-based learning stage. The argumentation skills of the students in the experimental class were better than the control class in argumentation components is evidence, rebuttal, and claim. The concept map instructional technique has aspects that can improve students' argumentation skill scores because it helps students focus on finding and connecting concepts based on evidence and data as a result of investigations